Além da cultura: uma casa, um projeto, três soluções - Yadira Coromoto Dias Neves (2016)
The comfort and energy performance of any building is heavily influenced by the local climate where it is located. In the countries where climates show remarkable temperature variations, it is necessary to adapt the buildings to the needs of their users, in order to provide them with quality of life and thermal comfort. When the urban profiles of some of the most important cities in the world are analysed, it´s possible to see a variety of models, building typologies and materials that, theoretically, are adapted to the climate in order to offer the best possible solution. Countries like the United States and Canada stand out due to the amount of buildings in pre-fabricated construction showing (wooden or metal houses, "fully adapted" to the climate, which offer comfort and quality to who dwells). Climates where temperatures range between 86 °F and - 104 °F. So, this type of construction should be possible to adapt to the environment in countries where the climate is less inclement. However, in Portugal, the overall image of the cities present a residential architectural language almost uniform, where the most remarkable difference between the buildings are due to the influence of existing architectural movement to the time of construction or the remodelling, not being able to show a large number of building that differ from the "traditional" block wall, with two or four waters covering. Thus, the object in question arises: what is the possibility of a strong cultural influence with the definition and selection of building typology to use? A comparison of various housing designs will help to analyse its thermal performance in a specific climate. This study uses computational tools for evaluation, in order to know their behaviour and compare the values obtained, and thus determine whether there is or not the prevalence of some of the models selected over others.